THE EFFECT UNEMPLOYMENT, EDUCATION AND THE NUMBER OF POPULATION ON THE POVERTY LEVEL IN BALI - Loka, Riska Dyah Puspita (Jurnal Ekonomi Kuantitatif Terapan, 2022)
Poverty is a condition involving the inability to meet economic prosperity as a minimum requirement of a certain standard of living. This study aims to analyze simultaneously and partially the effect of unemployment, education and population on the poverty level in the regency/city of Bali Province, as well as to analyze the variables with the dominant contribution in reducing poverty levels. The data analysis technique used is multiple linear analysis. The results of the analysis show that unemployment, education and population simultaneously have a positive and significant effect on the poverty level in the regency/city of Bali Province in the 2015-2020 period. The results show that unemployment and the population has a positive and significant effect on the poverty level, education has a negative and significant effect on the poverty level. The population has a dominant influence on the poverty level in regency/city in Bali Province in the 2015-2020.